2020
DOI: 10.1038/s41598-020-73968-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for effective selection of Interleukin-6 inhibitor and tumor necrosis factor inhibitor in the treatment of rheumatoid arthritis

Abstract: Treatment of rheumatoid arthritis (RA) is aimed at long-term remission and inhibition of joint destruction by different biologic drugs. However, the choice of a particular biologic agent based on individual cases of RA remains unestablished. Interleukin-6 (IL-6) inhibitor and tumor necrosis factor (TNF) inhibitor are common biologics used for the treatment of RA. This study aimed to investigate predictive factors for effective selection of tocilizumab (IL-6 inhibitor) and etanercept (TNF inhibitor) in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In addition, the TNF-α signalization blockade has also been done by inhibiting the TNF-α binding to its receptor through etanercept, a fully human soluble TNF receptor Fc fusion protein, where a dimer of the extracellular domains of human TNFR2 is fused to the Fc portion of human IgG1. The effectiveness of this drug has been established for the early administration from diagnosis of RA [57,58]. A phase IV study recently assessed the real-world safety and effectiveness of biosimilar etanercept in patients with RA, ankylosing spondylitis or psoriatic arthritis and receiving biosimilar etanercept injections, either 25 mg twice weekly or 50 mg once weekly [59].…”
Section: Anti-il-1β and -Tnf-α Therapies: Effects And Side Effects Of The Conventional Allopathic Dosesmentioning
confidence: 99%
“…In addition, the TNF-α signalization blockade has also been done by inhibiting the TNF-α binding to its receptor through etanercept, a fully human soluble TNF receptor Fc fusion protein, where a dimer of the extracellular domains of human TNFR2 is fused to the Fc portion of human IgG1. The effectiveness of this drug has been established for the early administration from diagnosis of RA [57,58]. A phase IV study recently assessed the real-world safety and effectiveness of biosimilar etanercept in patients with RA, ankylosing spondylitis or psoriatic arthritis and receiving biosimilar etanercept injections, either 25 mg twice weekly or 50 mg once weekly [59].…”
Section: Anti-il-1β and -Tnf-α Therapies: Effects And Side Effects Of The Conventional Allopathic Dosesmentioning
confidence: 99%
“…10 Hayashi S, et al, investigated biomarkers that help in selection of RA patients suitable for treatment with tocilizumab or etanercept and found that CRP, among other factors, positively correlated with improvement in clinical outcomes making it a suitable biomarker which helps the choice of patients for such therapy. 11 CRP/albumin ration (CAR) was studied by Sunar I, et al, who demonstrated that CAR was weakly associated with RA disease activity. 12 Furthermore, CAR was also reported by He Y et al, to be significantly increased in RA patients (p<0.01) and positively correlated with CRP (Spearman's correlation = 0.99) suggesting that it could be used as an indicator of RA inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…10 In another study, CRP has also been found to be a useful prognostic marker for response to tocilizumab treatment. 11 However, this study was limited as 196 patients were divided into 4 smaller subgroups limiting its statistical power. CAR was shown to be correlated with disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine plays a critical role in both the pathogenesis of active RA as well as the secretion of hepcidin from hepatocytes. 28,29 Due to its actual release from muscle cells (myonectin), the value of ERFE in human diseases is not restricted to anemia. In addition to being elevated in β-thalassemia major patients and associated with iron overload, 30,31 it has also been studied in CKD where EPO is the main treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine plays a critical role in both the pathogenesis of active RA as well as the secretion of hepcidin from hepatocytes. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%